Systematic review of the evidence of interoceptive awareness in performers - Pedraza Ramirez, Ismael (2016)
Ismael Pedraza, 2016. Systematic review of the evidence of interoceptive awareness in performers. Master s thesis in Sport and Exercise Psychology. Department of Sport Sciences. University of Jyväskylä. Pp. 53.